TINDAK TUTUR DIREKTIF DAN EKSPRESIF PADA TEKS FILM RUDY HABIBIE (HABIBIE & AINUN 2) KAITANNYA DENGAN SOSIAL DAN BUDAYA - Hayatul Mursida (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2020)
This research aims to obtain an objective description of (1) Describing the form and function of the directive and its relation to social and cultural in the text of Rudy Habibie (Habibie & Ainun 2). (2) Describe the form and function of expressive speech and its relation to social and cultural in the text of Rudy Habibie (Habibie & Ainun 2). To achieve that goal, the approach used in this study is to use a qualitative approach and use descriptive methods. This research data is in the form of verbal data, which is a derivative of the characters in the film Rudy Habibie (Habibie & Ainun 2). The data collection techniques used by researchers in this study are similar, note, and descriptive. The form of action directive in Rudy Habibie (Habibie & Ainun 2) includes: (a) the action of the directive of the request in the form of invitations, requests, and invitations marked with the words "come" and "come", (b) the action of the question directive, i.e. in the form of orders in the form of questions, (c) the action of the directive in the form of orders, namely the orders that are said directly and clearly and shown to the speech partners, (d) the prohibition directive is an order prohibiting a person, (e) the act of speech of the advice directive, (f) the act of speech of the directive of decency. Meanwhile, the form of expressive speech in Rudy Habibie (Habibie & Ainun 2) includes: (a) expressive speech in the form of expressions of pleasure or praise, for example, marked with the word "very good" (b) expressive speech in the form of displeased, (c) expressive speech in the form of an apology marked with the word "sorry" or "forgiveness", (d) expressive speech in the form of worry that serves to express one's concerns either indirectly or directly, (e) expressive speech in the form of expressions of sadness that serve to express one's sadness. Keywords: speech, directives, expressive, social, and cultural actions.